Bladder Chondrosarcoma in A Male: A Rare Case Report - Tamrin, Muhammad Husni; Djatisoesanto, Wahjoe (Folia Medica Indonesiana, 2021)
Chondrosarcoma is a rare variant of bladder tumor and one of the rare types of soft tissue sarcoma. This case happened on a 36-year-old male who complained of lumps in his lower abdomen, accompanied by difficulties in passing urine and painful urination, without hematuria. We performed TURBT and histopathological examination showed low-grade chondrosarcoma. The patient was diagnosed with low-grade bladder chondrosarcoma. The patient was treated for chemotherapy and radiotherapy. However, after undergoing one cycle of chemotherapy, the patient refused to continue the therapy.